Spatial and Functional Dynamics of Suburban and Rural Zones in the Kyiv Metropolitan Area amid Global and Military Challenges - Nagirna, V. P.; Rudenko, L. H. (Ukrainian Geographical Journal, 2025)
The article analyzes the impact of Kyiv’s metropolitan influence, geopolitical transformations, and climatic changes on rural territory during the period of Russian aggression. We identified features of the integral potential of the territory and Kyiv’s suburban area within it. A regional analysis of the structure and specialization of the rural sector, the localization of enterprises, and infrastructure development had also been done. The consequences of russia’s military invasion have been determined. Our article is dedicated to changes in the rural production, the functions of suburban rural areas, and the verification of the reconstruction and development of rural suburbs. The metropolis plays a central role among the factors influencing suburban and rural areas, and it has an impact on production activities, the employment of peasants, their incomes, and their infrastructure. The primary rural area’s main resources are human potential and its logistics system. Typically, land is utilized for agricultural development and as a territorial base for the construction of economic and social facilities, engineering, and transportation infrastructure. The primary pressure on the natural environment is most evident in suburban and rural areas. The spatial expansion of the metropolis leads to depletion of land resources, depreciation of human capital, deterioration of the ecological state, and increased migration of the rural population. The central development branch of suburban rural areas is agriculture. The leading crops are cereals and legumes, with the primary technical crop being sunflowers. But we also have a problem here. The growing of vegetables, fruit, and berry growing, and potatoes are losing their positions as important and traditional suburban industries. Suburban agriculture status changed to soil-depleting. Preference was given to highly efficient production aimed at increasing the profitability of agriculture. The characteristic of suburban rural settlement is increased polarization of socio-economic development along the “center-periphery” line. The most developed are the settlements located close to the metropolis. The russian federation war against Ukraine is the reason for significant damage, destruction, and loss of life in the suburban area of ​​Kyiv. Now we are forced to restore the objects of everyday life, the economic development of the suburban rural area: buildings, critical infrastructure, hydraulic structures, and logistics. Hundreds of hectares of agricultural land need to be demined, cleared, and restored. A decrease in labor resources in the countryside is indeed a problem, and the employment of men in agriculture is essential, too. The primary development strategies for rural areas include improving agriculture, restructuring and specializing it, enhancing the role of food production in suburban areas, and implementing other innovations, in response to global demands for agricultural products